2021
DOI: 10.15809/irriga.2021v26n1p1-12
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Allows to Estimate Water Stress and Yield Losses of Bean Cultivars

Abstract: REMOTE SENSING ALLOWS TO ESTIMATE WATER STRESS AND YIELD LOSSES OF BEAN CULTIVARS     DANIEL SOARES ALVES1; PABLO RICARDO NITSCHE1; VANIA MODA CIRINO2; MARIA BRIGIDA DOS SANTOS SCHOLZ1; JOSÉ DOS SANTOS NETO2 E PAULO HENRIQUE CARAMORI1   1 Área de Agrometeorologia, Ecofisiologia e Tecnologia de Alimentos, Instituto de Desenvolvimento Rural do Paraná IAPAR – EMATER, Rod. Celso Garcia Cid, 375, Conjunto Ernani Moura Lima II, 86.047 – 902, Londrina, Paraná, Brasil. danielsoares@idr.pr.gov.br; pablo.nitsche@idr.pr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…Anthocyanins are dark blue pigments with a photoprotective role that increases biosynthesis, and concentrations are often reported under stressful conditions [ 6 ]. Other authors have reported similar results with different bean cultivars where reflectance values (visible spectrum, far red, and near infrared) were higher in treatments under full irrigation compared to treatments exposed to water stress [ 49 ]. An increase in anthocyanin content, reduced leaf area, and other structural and morphological changes probably play a role in protecting the light-harvesting apparatus and the photochemistry of the plants grown under drought treatments.…”
Section: Discussionsupporting
confidence: 63%
“…Anthocyanins are dark blue pigments with a photoprotective role that increases biosynthesis, and concentrations are often reported under stressful conditions [ 6 ]. Other authors have reported similar results with different bean cultivars where reflectance values (visible spectrum, far red, and near infrared) were higher in treatments under full irrigation compared to treatments exposed to water stress [ 49 ]. An increase in anthocyanin content, reduced leaf area, and other structural and morphological changes probably play a role in protecting the light-harvesting apparatus and the photochemistry of the plants grown under drought treatments.…”
Section: Discussionsupporting
confidence: 63%
“…Técnicas de SR foram aplicadas porAlves et al (2021) para analisar o estresse hídrico da cobertura vegetal em áreas de cultura no estado do Paraná. Os autores destacaram que as técnicas de SR constituem ferramentas eficientes na análise do déficit hídrico da região concluindo que a resposta espectral se correlaciona com a produtividade e possibilita identificar o status hídrico da cobertura analisada.…”
unclassified